A Qur'anic View on Overcoming the Modern Muslim Identity Crisis: Syahrur's Naẓariyyah al-Ḥudūd Theory as a Dynamic Hermeneutical Paradigm - Ahmad Muwahidah; Mochamad Tholib Khoiri Waro (UIN Raden Mas Said Surakarta, 2024)
The modern Muslim identity crisis, marked by tensions between traditional religious values and the demands of modernity such as democracy and gender equality, is further exacerbated by globalization and digitalization. This study aims to examine Muhammad Syahrur’s Naẓariyyah al-Ḥudūd theory as a dynamic hermeneutical paradigm to address Muslim identity dissonance. The methodology combines Qur’anic textual analysis, ethnographic fieldwork in Islamic boarding schools, and comparative case studies of contextualized curricula in Morocco and Indonesia. The findings reveal that the concept of limit (ḥudūd) enables adaptive reinterpretations of inheritance and polygamy laws based on sharia goal (maqāṣid al-syarīah), redefines the principles of taqwā (guarding from sin by obedience) and fiṭrah (nature of origin) as foundations for inclusive Muslim identity, and demonstrates the effectiveness of integrating Qur’anic values into religious education, with 70% of students successfully merging religious and national identities. The scholarly contribution lies in reconciling the textualist-contextualist divide, expanding the application of maqāṣid al-syarīah to contemporary issues, and offering a transformative education model grounded in dynamic hermeneutics that is highly relevant to modern global challenges.